El buscador google y su incidencia en el autoaprendizaje de los estudiantes del décimo año de básica de la unidad educativa “Eugenio Espejo” de la ciudad de Babahoyo, provincia los Ríos, periodo 2016 - Piza Vargas, Wilson Geovanny (2017)
The network of Internet computers, using the vast and growing construction of computers and telecommunications in our province, has spread rapidly throughout the province and country, both in geographical extent and between different economic and social strata. For companies, immersed in our economy, it is increasingly essential to use this channel of communication, advertising and commerce, through which are disclosed the services and products that can be negotiated for the purpose of carrying out any sale. Personally you can discover in the enormous possibilities of negotiation through social networks. The functions of the Internet have allowed the reach of quick access of the information to keep in touch with each of the sectors that satisfy the communication needs and the information of the people, the institutions and the companies. At the local level, the present research focuses on the use of Web 2.0 technology applied to education. To carry out, he performed an analysis of the tools of the aforementioned technology during the student learning process, so he applied to design and apply, on the one hand a tool use measurement tool, and On the other The application of an instrument for the diagnosis of learning styles. Through statistical analysis you can determine the preferences of using these tools according to each style of learning. The obtained results demonstrate the importance of the users to establish a relationship with the learning styles, thus facilitating the integration of the tools in the educational process of each of the students.